Financial Management of Sapugara Bree Village, West Sumbawa Regency Based on the Perspective of Good Governance Principles - Pebriaty, Ade Evi; Supeno, Eko; Irianto, Jusuf (Universitas Teuku Umar, 2025)
The purpose of this study is to analyze how village financial management in Sapugara Bree Village, West Sumbawa Regency in Fiscal Year 2022. The informants in this study were selected by using purposive techniques. Data analysis in this study uses the Perspective of Good Governance Principles, namely by analyzing the fulfillment of the criteria of Good Governance principles, namely participation, transparency and accountability (Addink, 2013) which is elaborated with the Minister of Home Affairs Regulation Number 18 of 2020 concerning Village Financial Management at the stages of planning, implementation, administration, reporting, and accountability for the management of Sapugara Bree Village Finance for Fiscal Year 2022. The results of this study show that the financial management of Sapugara Bree Village for Fiscal Year 2022 has not met the criteria of Good Governance principles, especially at the stages of implementation, administration, reporting and accountability. This is due to the Village Head and Village Officials who ignore village financial management in accordance with applicable regulations. Many improvements are still needed, both in terms of integrity and human resources from Sapugara Bree Village, the development of a transparent, accountable, informative and interactive village website that supports supervision by the community, increased participation of the Village Consultative Body and related Regional Apparatus Organizations in carrying out guidance and supervision and the need for the formulation of policies or regional regulations that contain binding rewards and punishments related to participatory, transparent and accountable village financial management to encourage the performance of village apparatus in implementing village development activity programs in accordance with applicable regulations.